PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA MARKETPLACE LAZADA PRODUK 3SECOND - Indra Samuel (CV. Adiba Aisha Amira, 2025)
This study aims to analyze both the partial and simultaneous effects of independent variables, namely product quality (X1) and price (X2), on the dependent variable, which is customer satisfaction (Y). The research employs a quantitative approach, utilizing a simple random sampling technique based on Slovin's formula for sample calculation. The respondents in this study are consumers who have purchased 3Second products through the Lazada marketplace, with a total sample size of 100 participants. Data processing is conducted using SPSS software version 27. Based on the results of the partial test (t-test), product quality has a significant effect on customer satisfaction, with a t-value of 2.092, which is greater than the t-table value of 1.660, and a significance level of 0.039, which is below the threshold of 0.05. Similarly, the price variable has a significant impact on customer satisfaction, with a t-value of 2.013, exceeding the t-table value of 1.660, and a significance level of 0.047, which is less than 0.05. Meanwhile, in the simultaneous test (F- test), both independent variables—product quality (X1) and price (X2)—together have a significant influence on customer satisfaction (Y), with an F-value of 6.252, which is higher than the F-table value of 3.09, and a significance level of 0.003, which is below 0.05. Additionally, the determination test (R²) results indicate that the correlation between product quality (X1) and price (X2) with customer satisfaction (Y) reaches 89.3%.